Penjatuhan Sanksi Rehabilitasi Oleh Kepolisian Terhadap Penyalahguna Narkotika - Alfian, Deni Muhamad (Universitas Jabal Ghafur, 2025)
Rehabilitation sanctions are an effort to restore and restore the condition of narcotics users so that they return to physical, psychological, social and spiritual/religious (faith) health. With the conditions after undergoing rehabilitation, it is hoped that they will be able to return to living in society better and free from the trap of narcotics. The problem discussed in this research is how to impose rehabilitation sanctions as a measure to prevent the recurrence of narcotics abusers? What is the role of the police in handling and eradicating narcotics abusers? Normative juridical research methods. In conclusion, rehabilitation for narcotics abusers is carried out through medical rehabilitation and social rehabilitation. Placement in rehabilitation institutions can be done through investigators, public prosecutors, judges based on recommendations from a team of doctors or through recommendations from an assessment team. Rehabilitation can be carried out by government agencies or the community that meets standard service procedures. Apart from that, rehabilitation is also carried out for narcotics abusers as a further rehabilitation measure in an effort to improve addicts and/or victims of narcotics abusers so that they do not repeat their mistakes again. The role of the police in dealing with narcotics abusers today is by preventing the distribution of narcotics by carrying out activities such as coaching programs, prevention programs, treatment programs, healing efforts and enforcement programs by producers, dealers, dealers and users in order to make Indonesia free from narcotics abuse.Keywords : Narcotics, Sanctions, Rehabilitation